2021
DOI: 10.1002/jcp.30387
|View full text |Cite
|
Sign up to set email alerts
|

IκB kinase inhibition remodeled connexins, pannexin‐1, and excitatory amino‐acid transporters expressions to promote neuroprotection of galantamine and morphine

Abstract: Inflammatory pathway and disruption in glutamate homeostasis join at the level of the glia, resulting in various neurological disorders. In vitro studies have provided evidence that membrane proteins connexions (Cxs) are involved in glutamate release, meanwhile, excitatory amino-acid transporters (EAATs) are crucial for glutamate reuptake (clearance). Moreover, pannexin-1 (Panx-1) activation is more detrimental to neurons. Their expression patterns during inflammation and the impacts of IκB kinase (IKK) inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…These results suggest that baicalin exerts therapeutic effects on UC by inhibiting the IKK/IKB/NF-κB signaling pathway and apoptosis-related proteins [ 51 ]. However, Magdy et al indicated that the NF-κB pathway alleviated glutamate accumulation and neuronal cell damage by regulating the expression of membrane proteins (connexins (Cxs), Panx1, and excitatory amino-acid transporters) in the brain tissue [ 107 ]. Baicalin (25, 50, and 100 mg/kg bodyweight) protected against trinitrobenzenesulfonic acid (TNBS)-induced UC in rats by inhibiting the upregulation of ROS and MDA in the colon tissue of rats, downregulation of the GSH and SOD levels, and modulation of Th17/T regulatory (Treg) cell balance, gut microbiota, and SCFAs [ 52 ].…”
Section: Effects Of Baicalin Functions On the Gut–brain Axismentioning
confidence: 99%
“…These results suggest that baicalin exerts therapeutic effects on UC by inhibiting the IKK/IKB/NF-κB signaling pathway and apoptosis-related proteins [ 51 ]. However, Magdy et al indicated that the NF-κB pathway alleviated glutamate accumulation and neuronal cell damage by regulating the expression of membrane proteins (connexins (Cxs), Panx1, and excitatory amino-acid transporters) in the brain tissue [ 107 ]. Baicalin (25, 50, and 100 mg/kg bodyweight) protected against trinitrobenzenesulfonic acid (TNBS)-induced UC in rats by inhibiting the upregulation of ROS and MDA in the colon tissue of rats, downregulation of the GSH and SOD levels, and modulation of Th17/T regulatory (Treg) cell balance, gut microbiota, and SCFAs [ 52 ].…”
Section: Effects Of Baicalin Functions On the Gut–brain Axismentioning
confidence: 99%
“…However, we are cognizant that in recent years, many studies have shown that morphine can also exert neuroprotective effects through various mechanisms [ 28 ]. The main mechanisms include reducing intracellular Ca 2+ overload, reducing cell oxidative damage, activating autophagy, and inhibiting intracellular toxic protein production to promote neuronal regeneration and differentiation [ 29 , 30 , 31 , 32 ]. At the same time, researchers have applied very low doses of morphine to very preterm infants, which has effectively improved the neurodevelopmental status of the infants [ 33 ].…”
Section: Isoquinoline Alkaloids With Neuroprotective Effectsmentioning
confidence: 99%
“…Immunohistochemical assessment of the macrophage phenotype markers CD8, CD68, and CD 163 and the microglial marker Iba-1 was performed using the avidin-biotin peroxidase method as described previously (Magdy et al, 2021). Briefly, paraffin-embedded brain sections were dewaxed in xylene, rehydrated in a decreasing alcohol gradient, and microwave-treated (0.01 M trisodium citrate), for antigen retrieval.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%